AUDIT KOMUNIKASI VIRTUAL EXHIBITION PERTUNJUKAN SUMONAR FESTIVAL 2020 - Windri Saifudin; Farikha Rahmawati; Andisa Rizky Febrianti; Dewi Ratih (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Themed "Mantra Lumina" The Art of Light Performance held by SUMONAR has a very deep meaning, both for all parties involved in the festival and for the entire community who are still surviving in the midst of the Covid-19 Pandemic. The SUMONAR Festival is still present in the Virtual Exhibition 360 concept, the developments that continue to occur in the world of information technology are the reason for making this research. Aims to audit the communication process of the light arts show program and its future opportunities. The research method used is an evaluation method using a communication audit approach. This research design uses the five main stages of the Northwest Npower approach. The results of the communication audit stated that the implementation of SUMONAR FEST 2020 was going well by utilizing virtual exhibitions and website 360 ​​media as the venue for the event and in accordance with applicable public communication rules. Although, there were some shortcomings that occurred, such as the lack of monitoring instruments during the event, lacking the attention of the audience on social media to attend. The recommendations given sharpen the instrument for monitoring events and are expected to further develop Vitual Exhibition 360 by implementing virtual reality 360 technology for alternative art performances in the future.